KUALITAS AIR, KELANGSUNGAN HIDUP DAN PERTUMBUHAN BENIH IKAN GABUS (Channa striata) YANG DIPELIHARA DALAM MEDIA DENGAN PENAMBAHAN PROBIOTIK - Sri Hartini; Ade Dwi Sasanti; Ferdinand Hukama Taqwa (Jurnal Akuakultur Rawa Indonesia, 2013)
The aims of this research were to study the influence of probiotics on water quality of cultivation media, survival rate and growth of snakehead, and to determine the right concentration of probiotics to obtain the best water quality, survival rate and growth. This current research examined 6 treatments and each treatments was replicatet 3 times. The treatmens were randomized according to comletely randomized design.  The treatmens consisted of P0 (without probiotic addition), P1 (addition of 2.5 µl.l-1 week-1), P2 (addition of  5 µl.l-1 week-1), P3 (addition of 7.5 µl.l-1 week-1), P4 (addition of 10 µl.l-1 week-1) dan P5 (addition of 12.5 µl.l-1 week-1). The research was carried out for 30 days of maintenance in a tarp as a media container maintenance. From the research that has been done that the addition of probiotics in snakhead (C. striata)  maintenance media  obtained the best dose that is 10 μl.l-1 week-1.  Results of water quality measurements that include DO, temperature, pH, Ammonia, Nitrite and Nitrate in descriptive unreal influence.  But it gives a significantly different effect mainly on the total bacterial, survival rate (96.66%), with growth in the length of 1.3 cm and 0.27 g weight gain.   Key Word: Snakehead Larvae, Probiotics, Survival Rate, Growth